Experiencing Tess of the d'Urbervilles : A Deweyan Account - Efron, Arthur (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
This book interprets Thomas Hardy's Tess of the D'Urbervilles with the openness toward experience recommended by John Dewey's Art as Experience . The characters of Tess are considered as real people with sexual bodies and complex minds. Efron identifies the "experience blockers" that the critical tradition has stumbled upon, and defends Hardy's involvement in telling his story. Efron offers a new way of evaluating literature inspired by Dewey's pragmatist aesthetics.